2009
DOI: 10.1161/circulationaha.108.823740
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of CD11c + Monocytes in Atherogenesis Associated With Hypercholesterolemia

Abstract: Background-Monocyte activation and migration into the arterial wall are key events in atherogenesis associated with hypercholesterolemia. CD11c/CD18, a ␤ 2 integrin expressed on human monocytes and a subset of mouse monocytes, has been shown to play a distinct role in human monocyte adhesion on endothelial cells, but the regulation of CD11c in hypercholesterolemia and its role in atherogenesis are unknown. Methods and Results-Mice genetically deficient in CD11c were generated and crossbred with apolipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
244
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(274 citation statements)
references
References 28 publications
(49 reference statements)
18
244
2
3
Order By: Relevance
“…However, a recent study using the Ldlr Ϫ / Ϫ mouse model have demonstrated that the majority of intimal lipids in nascent lesions were located within foam cells that express CD11c ( 5 ), a marker widely used as a specifi c marker for murine DCs. CD11c is in fact also expressed by several tissue macrophages ( 46 ) as well as monocytes in models of atherosclerosis ( 47 ). CD11c + circulating monocytes can be activated by intracellular lipid accumulation prior to their recruitment to athero-prone regions of the vasculature, confusing the issue of what are CD11c + foam cytokine, which may be further enhanced by infl ammasome activation, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study using the Ldlr Ϫ / Ϫ mouse model have demonstrated that the majority of intimal lipids in nascent lesions were located within foam cells that express CD11c ( 5 ), a marker widely used as a specifi c marker for murine DCs. CD11c is in fact also expressed by several tissue macrophages ( 46 ) as well as monocytes in models of atherosclerosis ( 47 ). CD11c + circulating monocytes can be activated by intracellular lipid accumulation prior to their recruitment to athero-prone regions of the vasculature, confusing the issue of what are CD11c + foam cytokine, which may be further enhanced by infl ammasome activation, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes do express scavenger receptors (SRs) to some degree ( 5-7 ) and are exposed to hypercholesterolemic conditions during disease state. Recent studies in mice and in hypercholesterolemic patients have shown lipid accumulations in blood monocytes (8)(9)(10), but the consequences of cellular lipid accumulation, which have been well characterized in macrophages, are still unclear in monocytes.…”
mentioning
confidence: 99%
“…13 During atherogenesis, CD11c expression on aortic CD11b + myeloid cells increases. 14,15 This cell type is capable of both lipid phagocytosis and antigen presentation [14][15][16][17] and can productively interact with T cells in the murine aorta. 18 In moderate renal impairment, aortic CD11b + CD11c + myeloid cell numbers expand significantly.…”
mentioning
confidence: 99%